Retinal vessel analysis (RVA) in the context of subarachnoid hemorrhage: a proof of concept study - Albanna, Walid; Seiz-Rosenhagen, Marcel (PLOS ONE, 2016)
Background Timely detection of impending delayed cerebral ischemia after subarachnoid hemorrhage (SAH) is essential to improve outcome, but poses a diagnostic challenge. Retinal vessels as an embryological part of the intracranial vasculature are easily accessible for analysis and may hold the key to a new and non-invasive monitoring technique. This investigation aims to determine the feasibility of standardized retinal vessel analysis (RVA) in the context of SAH. Methods In a prospective pilot study, we performed RVA in six patients awake and cooperative with SAH in the acute phase (day 2-14) and eight patients at the time of follow-up (mean 4.6±1.7months after SAH), and included 33 age-matched healthy controls. Data was acquired using a manoeuvrable Dynamic Vessel Analyzer (Imedos Systems UG, Jena) for examination of retinal vessel dimension and neurovascular coupling. Results Image quality was satisfactory in the majority of cases (93.3%). In the acute phase after SAH, retinal arteries were significantly dilated when compared to the control group (124.2±4.3MU vs 110.9±11.4MU, p<0.01), a difference that persisted to a lesser extent in the later stage of the disease (122.7±17.2MU, p<0.05). Testing for neurovascular coupling showed a trend towards impaired primary vasodilation and secondary vasoconstriction (p = 0.08, p = 0.09 resp.) initially and partial recovery at the time of follow-up, indicating a relative improvement in a time-dependent fashion. Conclusion RVA is technically feasible in patients with SAH and can detect fluctuations in vessel diameter and autoregulation even in less severely affected patients. Preliminary data suggests potential for RVA as a new and non-invasive tool for advanced SAH monitoring, but clinical relevance and prognostic value will have to be determined in a larger cohort.
Gesehen am 02.07.2019